Categorization Of Open Actions In Management Implementation Plans. (Policy Papers; Policy Paper ;, 2020)
This paper undertakes a triage of the backlog of open actions in Management Implementation Plans (MIPs) responding to recommendations by the Independent Evaluation Office (IEO), based on the Framework endorsed by the Board in March 2019.